Leukocytic platelet rich fibrin (L-PRF) versus subepithelial connective tissue graft (SCTG) using tunneling technique in treatment of gingival recession: Randomize controlled clinical study - JOUNI, Joulia; BADR, Ahmed; ABOELSAAD, Nayer (International Arab Journal of Dentistry (IAJD), 2023)
Introduction: Gingival recession is a problem encountered daily in clinical practice, its etiology is often a multifactorial one. Surgical treatment is the only method to reverse this condition. Objective: to evaluate the effectiveness of leukocytic platelet rich fibrins (L-PRF) versus subepithelial connective tissue graft (SCTG) in the management of recession defects Miller’s class I or II (RT1) using the tunnel technique (TUN). Methods: 20 systemically healthy patients were allocated randomly to TUN with L-PRF (group A), and TUN with SCTG (group B). Probing depth, clinical attachment level, recession depth, width of keratinized tissue, gingival thickness, and recession esthetic score and wound healing index are clinical variables measured at baseline,14 days, 3 months, and 6 months postoperatively. Results: Significant improvement in mean CAL, and RD for both groups, and significant difference in GT and WKT for group B as well as higher RES. A significant difference was also recorded in group A for WHI Conclusions: Both grafting modalities in combination with tunnel technique improved gingival phenotype switching. Although SCTG gives higher esthetic and functional results including better color matching, tissue contour and increased width of keratinized tissue, L-PRF has superior healing properties and can be used as an alternative to treat multiple gingival recession defects where the need of second surgical site is eliminated.